Meta-analysis of association between K469E polymorphism of the ICAM-1 gene and retinopathy in type 2 diabetes - Wen-Ying Fan; Ning-Pu Liu (International Journal of Ophthalmology, 2015)
AIM:To collectively evaluate the association of intercellular adhesion molecule-1 (ICAM-1) gene K469E polymorphism (rs5498) with diabetic retinopathy (DR) in patients with type 2 diabetic mellitus (T2DM).METHODS:Overall review of available literatures relating K469E polymorphism to the risk of DR was conducted on 4 electronic databases. Meta-analysis was performed by Stata 12.0 to calculate pooled odds ratios (ORs). Potential sources of heterogeneity and bias were explored.RESULTS:Seven studies with genotype frequency data including 1120 cases with DR and 956 diabetic controls free of DR were included. Meta-analysis did not show significant association of K469E polymorphism with DR (P>0.05). A statistically significant association was detected between the K469E polymorphism and proliferative diabetic retinopathy (PDR) in Asians only in dominant model (GG+AG vs AA) with pooled OR of 0.729 (95%CI:0.564-0.942, P=0.016, Pheterogeneity=0.143), however, this association was not detected in recessive model (GA+AA vs GG; OR=1.178, 95%CI:0.898-1.545, P=0.236, Pheterogeneity=0.248) or allelic model (G vs A; OR=0.769, 95% CI:0.576-1.026, P=0.074, Pheterogeneity=0.094). No publication bias was found by Funnel plot, Begg''s and Egger''s test.CONCLUSION:This research found no statistically significant association between ICAM-1 gene K469E polymorphism and DR in patients with T2DM, but showed significant association of the K469E polymorphism with PDR in Asian diabetic patients only in dominant model. Further investigation would be required to consolidate the conclusion.